2020
DOI: 10.1097/wad.0000000000000385
|View full text |Cite
|
Sign up to set email alerts
|

Physical Exercise and Longitudinal Trajectories in Alzheimer Disease Biomarkers and Cognitive Functioning

Abstract: Introduction: Associations of physical exercise with Alzheimer disease (AD) biomarkers and cognitive functioning have been observed cross-sectionally. However, the effects of exercise on longitudinal change in AD biomarkers have not been thoroughly investigated. The current study examined whether individuals with higher baseline exercise exhibited less longitudinal change in AD biomarkers and cognitive functioning, and whether APOE and/or brain-derived neurotrophic factor (BDNF) genotypes moderated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 36 publications
1
19
0
Order By: Relevance
“…Of the two studies assessing tau, one (Liang et al, 2010) found no main effects of physical activity and APOE on either tau or phosphorylated tau, and it did not investigate outcomes stratified by APOE. The other (Stojanovic et al, 2020) found a main effect of APOE, with e4 carriers having higher levels of both tau and phosphorylated tau. However, physical activity was not associated with tau or phosphorylated tau in e4 carriers or non-carriers.…”
Section: Taumentioning
confidence: 90%
See 1 more Smart Citation
“…Of the two studies assessing tau, one (Liang et al, 2010) found no main effects of physical activity and APOE on either tau or phosphorylated tau, and it did not investigate outcomes stratified by APOE. The other (Stojanovic et al, 2020) found a main effect of APOE, with e4 carriers having higher levels of both tau and phosphorylated tau. However, physical activity was not associated with tau or phosphorylated tau in e4 carriers or non-carriers.…”
Section: Taumentioning
confidence: 90%
“…Two studies assessed cerebrovascular health indicated by WMH. One (Boots et al, 2015) Liang et al (2010), Head et al (2012), Brown et al (2013), Vemuri et al (2016), Jeon et al (2020), Stojanovic et al (2020), andTsai et al (2021 physical activity on WMH, with more active participants having lower WMH (better cerebrovascular health). There was no significant physical activity by APOE interaction, suggesting that both e4 carriers and non-carriers benefited from being physically active.…”
Section: Cerebrovascular Healthmentioning
confidence: 99%
“…Despite compelling evidence from animal models, clinical data of physical activity's influence on AD biomarkers are not that encouraging, along the cognitive continuum. In older adults who were clinically normal on the baseline, the intensity of self-reported physical activity did not modulate the rate of cerebrospinal fluid Aβ42 decrease, p-tau181, and total-tau increase, or the cortical Aβ accumulation [33]. In agreement, among clinically normal older participants, objectively measured physical activity was not associated with Aβ burden, although greater engagement in physical activity was prospectively associated with slower Aβ-related cognitive decline and gray matter volume loss [34].…”
Section: Article Highlightsmentioning
confidence: 77%
“…Although cerebrospinal fluid biomarkers and amyloid PET imaging are the most frequently applied modalities in this field, the applicability of plasma biomarkers is gradually improving. Many observational studies involving measures of Aβ in cerebrospinal fluid ( Liang et al, 2010 ; Brown et al, 2013 , 2017 ; Law et al, 2018 ), plasma ( Stillman et al, 2017 ), and PET ( Head et al, 2012 ; Brown et al, 2013 , 2017 ; Jeon et al, 2020 ; Treyer et al, 2021 ) have reported better profiles of amyloid-related biomarkers in active people but inconsistencies remain ( de Souto Barreto et al, 2015 ; Jeon et al, 2020 ; Palta et al, 2020 ; Stojanovic et al, 2020 ). The representative studies are summarized in Table 4 .…”
Section: Anti-neurodegenerative Mechanismsmentioning
confidence: 99%